Scleroderma : From Pathogenesis to Comprehensive Management - Varga, John; Denton, Christopher P.; Wigley, Fredrick M.; Allanore, Yannick; Kuwana, Masataka (Springer International Publishing : Imprint: Springer, 2017)
Comprised of the authoritative work of international experts, this fully-updated second edition of Scleroderma builds upon the well-regarded approach in the first edition to provide integrated, concise, and up-to-date synthesis of current concepts of pathogenesis and modern approaches to management of systemic sclerosis (scleroderma). With a multidisciplinary approach to comprehensive care, this book is easily accessible for health care professionals in many fields. The new edition includes extensive updated material based on major developments in the field, with new chapters on personalized medicine, cancer complications, global perspectives on scleroderma, and more. It presents a succinct and thoughtful synthesis of current pathomechanistic concepts, providing a valuable reference tool for basic and translational investigators working in the field. Scleroderma: From Pathogenesis to Comprehensive Management serves as an essential, all-inclusive resource for rheumatologists, pulmonologists, cardiologists, gastroenterologists, nephrologists and all those involved in the care of scleroderma patients.
Keywords: Medicine.; Dermatology.; Respiratory organs -- Diseases.; Rheumatology.; elektronické knihy; electronic books